Did Teachers' Remote Support Help Minority Parents?: The Associations among Home Activities, Teachers' Support and Parental Stress at the Onset of the COVID Pandemic. - Zhang, Chenyi; Li, Hongli; Aldib, Roula; Qiu, Wei (Journal of Child & Family Studies, 2025)
While the impact of the COVID-19 pandemic on family well-being has been extensively examined, the specific effects on families with young children during the initial stages of mandated physical distancing remain underexplored. This study delves into the relations among the demands of providing home activities, the availability of teacher support, and parents' psychological well-being (i.e., parental stress), taking into account the socio-economic status (SES) and ethnic backgrounds (Caucasian versus non-White minority) of the parents. A group of 212 parents of preschool-aged children (three to five years old) from the United States participated in the study. The parents reported their perceived stress levels, the frequency of various home activities, and the types of support they received from their children's teachers. Structural Equation Modeling (SEM) analyses revealed that physical distancing and parental stress were indirectly related through learning-focused home activities. While parents' annual income was identified as a risk factor for increased stress, higher educational levels appeared to mitigate stress, acting as a protective factor. The study observed distinct patterns of relations between these variables among the two ethnic groups. Learning-focused activities and teacher support were associated with higher stress levels among minority parents compared to their Caucasian counterparts. These findings underscore the need for culturally sensitive parenting support and the reinforcement of collaborations between early childhood professionals and parents as part of a comprehensive emergency response strategy.